The effect of mesenchymal stem cells and imatinib on macrophage polarization in rat model of liver fibrosis. (2nd October 2022) - Malmir, Ali; Farivar, Shirin; Rezaei, Ramazan; Tokhanbigli, Samaneh; Hatami, Behzad; Mazhari, Sogol; Baghaei, Kaveh
Abstract: Liver fibrosis is a disorder in which inflammatory reactions play an important role, and central to the progression and pathogenesis of this disease are the immune‐specific cells known as macrophages. Macrophage types are distinguished from each other by the expression of a series of surface markers. STAT6 and Arg1 play an important role in the polarization of macrophages, so these two factors are downstream of interleukin 4 (IL‐4) and IL‐13 cytokines and cause to differentiate M2. Therefore, this study aimed to compare the independent effects of imatinib and mesenchymal cell treatment on the polarization of macrophages in rat models of liver fibrosis. The liver fibrosis was induced by the injection of CCL4 for 6 weeks in Sprague–Dawley rats. Then, rats were divided into four different groups, and the effects of imatinib and mesenchymal cells on the expression of Arg1, Ly6c, and STAT6 were evaluated. Histopathology experiments considered the amelioration effect of treatments. Our results showed that Arg1 expression was significantly increased in the groups treated with mesenchymal cells and imatinib compared to the control group. On the other hand, expression of STAT6 was significantly increased in the imatinib‐treated mice compared to mesenchymal and control groups. Moreover, the expression of LY6C significantly decreased in imatinib and mesenchymal treated groups compared to the control group. Therefore, our data showed that mesenchymal stem cells and imatinib significantly modulate the fibrotic process in rat models of fibrosis, probably by polarizing macrophages towards an anti‐inflammatory profile and increasing the frequency of these cells in liver tissue.